Growth of Sesbania rostrata on Different Components of Tin Tailings - Othman, Radziah; Shamsuddin, Zulkifli (1990)
Two field experiments were conducted to evaluate the growth of Sesbania rostrata on sandy, sandy loam and slime components of a tin tailing area treated with inorganic fertilizer, and on the sandy component amended with an organic mixture. Inorganic fertilizer was applied at a rate of30 kg N, 90 kg P20sand 120 kg K20 ha -1. The organic mixture used consisted of50% palm oil mill cake (POMC) and 50% chicken dung at a total equivalent rate of10 t ha -1. Plants were harvested after 24, 42 and 63 days of growth. The results showed that S. rostrata grew best on the slime and poorest on the sandy tailings. Inorganic fertilization increased plant growth on the slime and sandy loam but not on the sandy tailings. Plant tops, roots and nodules in sandy soil amended with organic mixture were 29,27and 2.5 times bette'i than those with the inorganic fertilizer. Plant growth on sandy tailing was equivalent to 56% of plant tops and 200% of roots from plants grown on slime supplied with inorganic fertilizers.